The role of telecommunication standards in European integration. - Diamente, Cristina C. (University of Ottawa (Canada), 1997)
"The Role of Telecommunications Standards in European Integration" analyses the process of harmonisation for European telecommunications terminal equipment standards from 1958-1996. The M.A. Thesis focuses on Commission legislation dealing with telecommunications standards enacted in the Treaty of Rome up to the Maastricht Treaty with a special focus on the "New Approach to Technical Harmonisation and Standardisation". This thesis also looks at the application of the Low Voltage Directive 73/23/EEC and the Electromagnetic Compatibility Directive 89/336/EEC, and shows in practice, how European integration affected the national transposition of these directives into law and moreover, how the designated standards in these directives were harmonised. The final section assesses the implementation of European harmonised standards under the low voltage directive and electromagnetic compatibility directive into Member State legislation during 1996. And finally, in order to make a contribution to European Integration studies, the role of telecommunication standards is also placed within the framework of political European Integration Theory.
Keywords: History, European.